Composition and concentration dependences of electron mobility in semi-metal Hg₁₋xCdxTe quantum wells - Melezhik, E.O.; Gumenjuk-Sichevsk, J.V.; Sizov, F.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Modeled in this work is the electron mobility in the n-type Hg⁰.³²Cd⁰.⁶⁸Te/Hg₁₋xCdxTe/Hg⁰.³²Cd⁰.⁶⁸Te quantum well being in the semi-metal state at T = 77 K. Calculations take into account longitudinal polar optical phonon scattering, charged impurities scattering and electron-hole scattering. The Boltzmann transport equation has been solved directly to account the inelasticity of optical phonon scattering. Numerical modeling showed that the intrinsic electron mobility at liquid nitrogen temperature is sufficiently low. This mobility can be increased up to the values close to 10⁵…10⁶ cm² /(V·s) by increasing the electron concentration in the well. A higher electron concentration could be reached by doping the barriers or by applying the top gate voltage. The effect of mobility growth could be explained by the enhancement of 2DEG screening and the decrease of holes concentration.